A-Harmonic Equations and the Dirac Operator. (26th April 2010) - Nolder, Craig A.
Abstract : We show howA -harmonic equations arise as components of Dirac systems. We generalizeA -harmonic equations toA -Dirac equations. Removability theorems are proved for solutions toA -Dirac equations.